Discovering superior basal plane active two-dimensional catalysts for hydrogen evolution. (May 2019) - Zhang, Jing; Wu, Jingjie; Zou, Xiaolong; Hackenberg, Ken; Zhou, Wu; Chen, Weibing; Yuan, Jiangtan; Keyshar, Kunttal; Gupta, Gautam; Mohite, Aditya; Ajayan, Pulickel M.; Lou, Jun
Graphical abstract: Abstract: The emerging non-noble metal two-dimensional (2D) catalyst, such as MoS2, for the hydrogen evolution reaction (HER) is known to have an inert basal plane unless being converted to a metastable metallic phase or defect engineered. In order to take advantage of the majority of the material in such layered catalysts, fast screening of 2D catalysts with superior basal plane activity is imperative. A local electrochemical measurement method assisted by the e-beam lithography patterning was developed and applied to quantify the activity of basal planes of different layered transition metal dichalcogenides (TMDs) toward HER. This local measurement offers a robust platform to discover active TMDs fast and precisely. The construction of HER volcano plot leads to the discovery of superior basal plane active group VB metal disulfides, especially 3R-NbS2 . Interestingly, the trends found in the volcano plot imply distinctive differences in the mechanism of TMD catalysts compared to their metal counterparts. The intensive hydrogen evolution reaction in-between the basal planes drives self-nanostructuring in morphology of 3R-NbS2 . The increase in the effective surface area, and decrease in the electron-transfer resistance across the substrate and basal plane interface induced by the self-nanostructuring in turn enhances the HER performance of 3R-NbS2 . The 3R-NbS2 clearly stands out among non-noble metal catalysts for HER.